Safety and tolerability of once monthly aripiprazole treatment initiation in adults with schizophrenia stabilized on selected atypical oral antipsychotics other than aripiprazole. (October 2013) - Potkin, Steven G.; Raoufinia, Arash; Mallikaarjun, Suresh; Bricmont, Patricia; Peters-Strickland, Timothy; Kasper, William; Baker, Ross A.; Eramo, Anna; Sanchez, Raymond; McQuade, Robert
Abstract Objective: Safety and tolerability assessment of initiating treatment with a once monthly long-acting injectable form of aripiprazole (aripiprazole once monthly) in patients stabilized on oral antipsychotics other than aripiprazole. Methods: Patients with schizophrenia treated with oral atypical antipsychotics other than aripiprazole and with a history of aripiprazole tolerability were enrolled. Patients were stabilized per investigator's judgment for ≥14 days on oral atypical antipsychotics during screening. Patients then received one dose of aripiprazole once monthly (400 mg). Concomitant with aripiprazole once monthly, subjects received their current oral atypical antipsychotic for 14 ± 1 days at doses reduced to the mid/lower recommended dose range. Safety and tolerability were assessed for the 28-day treatment phase. For pharmacokinetic analyses, aripiprazole plasma concentrations were measured on Days 7, 14, and 28. Results: Sixty patients were enrolled and initiated with aripiprazole once monthly while continuing treatment with oral olanzapine (n = 3), quetiapine (n = 28), risperidone (n = 24) or ziprasidone (n = 5). Duration of co-administered oral antipsychotic treatment varied, ranging from 0 to 15 days. Treatment was well tolerated. Frequently reported treatment-emergent adverse events (TEAEs) were injection-site pain and toothache (4/60 subjects each, 6.7%), followed by dystonia, fatigue, increased blood creatine phosphokinase, insomnia and restlessness (3/60 subjects each, 5.0%). Most TEAEs occurred in the first 8 days of co-administration irrespective of days of oral overlap. No clinically relevant mean changes from baseline were observed for laboratory values or fasting metabolic parameters. Psychotic symptoms remained stable. Aripiprazole plasma concentrations were similar to those observed following daily doses of oral aripiprazole. Conclusions: The adverse-event profile of patients receiving aripiprazole once monthly concomitant with oral atypical antipsychotics other than aripiprazole was consistent with previous reports of aripiprazole once monthly concomitant with oral aripiprazole. Adverse events were similar irrespective of prior atypical antipsychotic and duration of oral antipsychotic overlap, suggesting that patients can be safely switched from their existing oral antipsychotic to aripiprazole once monthly without requiring an intermediate stabilization phase with oral aripiprazole. Aspects of the study design (open-label trial and short duration) and patient population (predominantly male and of African–American ethnicity) may limit the generalizability of these findings. Clinical trial registration: Safety and Tolerability Trial of Aripiprazole IM Depot Treatment in Adult Subjects With Schizophrenia Stabilized on Oral Antipsychotics Other Than Aripiprazole. ID number: NCT01552772. Registry: clinicaltrials.gov.